STRATEGI KEPALA SEKOLAH DAN ORANG TUA TERHADAP MUTU TAHFIDZ AL-QUR’AN ANAK DI PUSAT KEGIATAN BELAJAR MASYARAKAT SEKOLAH DASAR (SD) NAILUFAR JAKARTA TAHUN AJARAN 2023/2024 - Said, Ahmad; Al Mufti, Muflihin; Rofi’i, Ahmad (UNISAN JURNAL, 2025)
In an educational institution, there are many challenges faced in improving the quality of students' memorization of the Qur'an, both from within students and from the surrounding environment. Therefore, the role of school principals and parents is needed in developing strategies to improve the quality of children's memorization. The sample used in this study was 64 students of PKBM Nailufar Elementary School, Jakarta. This study aims to determine the strategies of principals and parents in improving the quality of children's memorization. The research is qualitative in nature and data collection by interview, observation and documentation. The strategies carried out by the principal are the integration of tahfidz in the school curriculum, supervision and evaluation of the tahfidz program as well as motivation and appreciation to students. The strategies carried out by parents are helping murojaah at home, creating an Islamic environment and providing motivation and rewards. The challenges in the tahfidz program at Nailufar Elementary School are children's difficulty in memorizing, limited time at school, and many variations in parental support. Based on the results of the study, it can be concluded that the principal's strategy and parental support have a significant influence on the quality of children's tahfidz. Principals who have a clear vision, implement a good evaluation system, and provide motivation to students tend to produce a more effective tahfidz program. On the other hand, active parental support in accompanying children's memorization at home also contributes greatly to the success of the tahfidz program. However, challenges in time constraints and variations in support from parents need further attention so that the quality of tahfidz can be optimized.